Tanggung Jawab Pemerintah Provinsi Nusa Tenggara Timur Dalam Pengananan Stunting - Maria Yensi Tamo Ina; Sutarno Sutarno; Sulaksono Sulaksono (Universitas Medan Area, 2023)
This study aims to analyze the Responsibilities of the East Nusa Tenggara Provincial Government in Treating Stunting. The research method uses normative juridical with a conceptual and legal approach. Presidential Regulation No. 42 of 2013 concerning the Acceleration of Nutrition Improvement may not be implemented properly due to regional autonomy which makes local governments have the authority to make their own policies regarding the health conditions of the people in their regions, Decree of the Governor of East Nusa Tenggara Number 324/KEP/HK/2018 concerning the Commission for the Acceleration Stunting Prevention in East Nusa Tenggara Province shows that the local government is very responsible in exercising its authority to overcome stunting in East Nusa Tenggara Province, Presidential Decree no. 72 of 2021 concerning the Acceleration of Stunting Reduction can reduce the number of stunting incidents because multi-stakeholder collaboration or partnerships are needed in efforts accelerating the reduction of stunting is a real action in overcoming the challenges of stunting in East Nusa Tenggara.